OXCT1 promotes triple negative breast cancer immune escape via modulating succinylation modification of PGK1 - Hongchen Zhang; Min Ling; Yuheng Zhang; Qing Fang; Wanlong Wo; Xiaoai Lv (Communications Biology)
Abstract Immunotherapy has made a breakthrough in triple negative breast cancer (TNBC). The aim of this study is to investigate the specific role and regulatory mechanism of 3-oxoacid CoA-transferase 1 (OXCT1) in influencing TNBC growth and immune escape induced by aerobic glycolysis. OXCT1-induced enhancement of TNBC cell proliferation and PD-L1 expression is reversed by 2-DG. After interference with OXCT1 in TNBC patient-derived organoids (PDOs), tumor cell proliferation and lactic acid secretion are attenuated, and T-cell killing is enhanced. OXCT1 correlates with phosphoglycerate kinase 1 (PGK1) protein expression in clinical TNBC samples. In vitro overexpression of OXCT1 has no significant effect on PGK1 mRNA expression, but increases the succinylation level of PGK1 K146 and its protein stability, while decreasing its ubiquitination. The H4K20me1 level in the OXCT1 promoter region is increased in TNBC tissues, and in vitro lysine methyltransferase 5 A (KMT5A) overexpression increases the H4K20me1 level in the OXCT1 promoter region to promote OXCT1 expression. In conclusion, OXCT1 interference reverses the KMT5A-induced enhancement of TNBC cell viability, proliferation, and PD-L1 expression. KMT5A promotes OXCT1 expression through histone methylation, and OXCT1 increases PGK1 protein stability through succinylation modification, thereby promoting aerobic glycolysis and immune escape in TNBC.